If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + x = 5a Solving a + x = 5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5a' to each side of the equation. a + -5a + x = 5a + -5a Combine like terms: a + -5a = -4a -4a + x = 5a + -5a Combine like terms: 5a + -5a = 0 -4a + x = 0 Add '-1x' to each side of the equation. -4a + x + -1x = 0 + -1x Combine like terms: x + -1x = 0 -4a + 0 = 0 + -1x -4a = 0 + -1x Remove the zero: -4a = -1x Divide each side by '-4'. a = 0.25x Simplifying a = 0.25x
| 10-4t=-6t | | 63-3=n-5 | | 2(3r-3)=-22+8r | | -8x+3=14 | | -53-9x=35-5x | | 26=x/-5 | | 4j-3=5j | | 5(-7-6n)=-10-5n | | x^2+4x+8=8x+29 | | 2x=.36 | | 5/9(240) | | 3/7+2/5x=1/5x+1 | | 9h+6=10h | | -28=-x+11-(-5) | | -1/5r=-20 | | 5(t+2)=3.2k | | p^2=3p+28 | | (2x+1)*2+(x+1/2)*2=18 | | 5x+10=30whatisx | | 3x-12+2x=13 | | 11.3-72f=-3.82 | | 2k+k=-9 | | 2k=-9k^2-10 | | 11y-7y-10=73.92 | | -x^2y= | | 3+7x-5=4x-12 | | 5p-12-3(p+8)=4 | | f(-3)=-2(3x-2)+x+9 | | 3-7(-2)-8= | | -7w=42 | | 15x+x=192 | | 20x^3+31x^2+12x=0 |